2013
DOI: 10.1016/j.ijid.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Anyplex™ II multiplex real-time PCR for the diagnosis of seven sexually transmitted infections: comparison with currently available methods

Abstract: Multiplex real-time PCR was found to be an equivalent or superior modality for the diagnosis of STIs. It could be a cost-effective and rapid diagnostic tool for the simultaneous detection of multiple STI microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
86
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 35 publications
2
86
0
4
Order By: Relevance
“…The formerly known U. urealyticum biovars, biovar 1 and biovar 2, were identified as separate species, U. parvum and U. urealyticum, respectively by polymerase chain reaction (PCR) (4). Ureaplasma spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formerly known U. urealyticum biovars, biovar 1 and biovar 2, were identified as separate species, U. parvum and U. urealyticum, respectively by polymerase chain reaction (PCR) (4). Ureaplasma spp.…”
Section: Introductionmentioning
confidence: 99%
“…with NGU depends on the species detected and that U. urealyticum, but not U. parvum, is an etiological agent in NGU (5). Furthermore, it has been reported that U. urealyticum can cause infections in the lower genital tract and is a pathogen of male urethritis (4,6). However, U. urealyticum has been reported as a probable cause of bacterial vaginosis, and there are limited data indicating that bacterial vaginosis might cause cervicitis in females (5).…”
Section: Introductionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) is an advanced molecular biology method, presenting high sensitivity and rapidity compared to traditional methods (culture-based and other standard methods) (11,12). Quick detection of these pathogens is important and mul- (14). Simultaneous detection of multiple pathogens using PCR amplification presents higher sensitivity and specificity compared to reference methods (14,15 …”
Section: Introductionmentioning
confidence: 99%
“…Quick detection of these pathogens is important and mul- (14). Simultaneous detection of multiple pathogens using PCR amplification presents higher sensitivity and specificity compared to reference methods (14,15 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, multiplex molecular assays have an additional advantage in screening and diagnosis since they enable simultaneous diagnosis of several sexually transmitted infections (STIs). Several commercial multiplex PCR kits have been developed, and a few studies have evaluated their performance …”
Section: Introductionmentioning
confidence: 99%